Pengaruh Penggunaan Obat Kortikosteroid Terhadap Kejadian Glaukoma Akut - Siti Shafira Elfreda; Rani Himayani; Putu Ristyaning Ayu Sangging (CV. Jasa Sukses Abadi, 2023)
Based on 2015 data obtained from the Global Burden of Disease Study, around 36 million people in the world or the global population are blind, 12.6 million of them are caused by cataracts, 7.4 million due to refractive disorders, and 2.9 million due to glaucoma. Corticosteroids are an anti-inflammatory class that is usually used in ocular and anterior segment disorders. When taking steroid drugs systemically or using them topically, periocular, or by inhalation, there will usually be an impact in the form of an increase in intraocular pressure which will show the effect within 3-6 weeks after use. This research was conducted as a type of literature review to collect data relevant to the material currently being studied, namely steroid-induced glaucoma. The results of the study showed that Steroid Induced Glaucoma is an eye disorder caused by steroid consumption and are the most common cause of irreversible blindness. This eye disorder is caused by systemic, inhaled, intranasal, or topical steroid induction which can cause an increase in IOP within several months. Treatment that can be recommended for patients to treat this case is with medication in the form of beta-blockers, alpha-2 agonists, and carbonic anhydrase inhibitors. It is also recommended for operative procedures such as lasers, tube shunts and cyclo-destructive procedures.